Analisis Komparasi Metode Pemetaan Ekosistem Mangrove Menggunakan Penginderaan Jauh dan Sistem Informasi Geografis - Rahma, Isma Yulia (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2020)
The use of tools and methods in mapping mangrove ecosystem continues to change.Nowday's trend in mapping is to use remote sensing and digital geographic Information system technology. There are several commonly used methods for mapping the mangrove ecosystem, but we should be aware that choosing the right method of analysis will greatly support the quality of research. The research method is literature review from various books and accredited scientific journals. Subsequently conducted analysis of application methods of mapping mangrove ecosystem of various case studies and research needs. Based on research, there are five methods and analysis used i.e.manual interpretation with Mirror stereoscope, NDVI (Normalized Difference Vegetation Index) as the most common analysis for mangrove distribution mapping. Multivariat PCA (Principal Component Analysis),Ã‚Â FCD (Forest Canopy Density)Ã‚Â model, and copmpare methods to mapping the extensive changes of mangrove ecosystems. Therefore, this article can be an input for the prospective mangrove ecosystem researchers in determining the preciese method of analysis.Ã‚Â Ã‚Â